A circRNA–mRNA pairing mechanism regulates tumor growth and endocrine therapy resistance in ER-positive breast cancer - Jia Yi; Jiao Du; Xue Chen; Rui-chao Nie; Guo-sheng Hu; Lei Wang; Yue-ying Zhang; Shang Chen; Xiao-sha Wen; Di-xian Luo; Hua He; Wen Liu (Proceedings of the National Academy of Sciences, 2025)
The molecular mechanisms underlying estrogen receptor (ER)-positive breast carcinogenesis and drug resistance remain incompletely understood. Elevated expression of CCND1 is linked to enhanced invasiveness, poorer prognosis, and resistance to drug therapies in ER-positive breast cancer. In this study, we identify a highly expressed circular RNA (circRNA) derived from FOXK2 , called circFOXK2, which plays a key role in stabilizing CCND1 mRNA, thereby promoting cell cycle progression, cell growth, and endocrine therapy resistance in ER-positive breast cancer cells. Mechanistically, circFOXK2 binds directly to CCND1 mRNA via RNA–RNA pairing and recruits the RNA-binding protein ELAVL1/HuR, stabilizing the CCND1 mRNA and enhancing CCND1 protein levels. This results in activation of the CCND1–CDK4/6–p-RB–E2F signaling axis, driving the transcription of downstream E2F target genes and facilitating the G1/S transition during cell cycle progression. Notably, targeting circFOXK2 with antisense oligonucleotide (ASO-circFOXK2) suppresses ER-positive breast cancer cell growth both in vitro and in vivo. Moreover, combination therapy with ASO-circFOXK2 and tamoxifen exhibits synergistic effects and restores tamoxifen sensitivity in tamoxifen-resistant cells. Clinically, high circFOXK2 expression is positively correlated with CCND1 levels in both ER-positive breast cancer cell lines and patient tumor tissues. Overall, our findings reveal the critical role of circFOXK2 in stabilizing the oncogene CCND1 and promoting cancer progression, positioning circFOXK2 as a potential therapeutic target for ER-positive breast cancer in clinical settings.